Cango Lyec (Healing the Elephant): Chronic Hepatitis B Virus among post-conflict affected populations living in mid-Northern Uganda. - Samuel S Malamba (Public Library of Science (PLoS), 2021)
Background The legacy of war in Northern Uganda continues to impact people's health and wellbeing in the Acholi region. Despite increasing attention to Hepatitis B Virus (HBV) in Uganda and globally, concerns remain that unique drivers of infection, and barriers to screening, and treatment, persist among those affected by conflict. Methods Cango Lyec (Healing the Elephant) cohort survey involved conflict-affected adults aged 13-49 in three mid-Northern Uganda districts (Gulu, Amuru and Nwoya). Baseline (2011-2012) samples were tested for HBV surface antigen (HBsAg), HBV e-antigen (HBeAg), antibodies to HBV surface antigen (HBsAb), antibodies to HBV e-antigen (HBeAb), and antibodies to HBV core antigen (HBcAb). All HBsAg positive samples were tested for IgM antibodies to HBV B core antigen (HBc-IgM) and where available, >6-month follow-up samples were tested for HBeAg and HBV DNA. Data were analyzed using STATA 15 software. Logistic regression accounted for variance due to complex two-stage sampling that included stratification, unequal selection probabilities and community clustering. Odds ratios measured effect potential risk factors associated with chronic HBV infection. Results Among 2,421 participants, 45.7% were still susceptible to HBV infection. HBsAg seropositivity was 11.9% (10.9-13.0), chronic HBV was 11.6% (10.4-12.8), acquired immunity resulting from vaccination was 10.9%, and prior natural infection was 31.5%. Older age (OR:0.570; 95%CI:0.368-0.883) and higher education (OR:0.598; 95%CI:0.412-0.868) were associated with reduced odds of chronic HBV infection. Being male (OR:1.639; 95%CI:1.007-2.669) and having been abducted (OR:1.461; 95%CI:1.055-2.023) were associated with increased odds of infection. Among women, having 1 or 2 pregnancies (compared to none or >2) was associated with increased odds of infection (OR:1.764; 95%CI:1.009-3.084). Conclusion Chronic HBV is endemic in Gulu, Amuru and Nwoya districts. Recommended strategies to reduce post-conflict prevalence include establishment of Northern Uganda Liver Wellness Centres, integration of screening and treatment into antenatal care, and roll out of birth-dose vaccination.